Assessment of information literacy skills and information-seeking behavior of medical students in the age of technology: a study of Pakistan. Issue 1 (11th February 2021) - Haider, Mohammad Sohail; Ya, Chen
Abstract : Purpose: Information literacy skills (ILSs) and information-seeking behavior (ISB) is a widespread topic that needs modern technologies to improve the technical skills of the students. The purpose of this study is to assess the usage of library resources for medical college students. To explore and understand the student's level of satisfaction, learning and seeking behavior by efficient information retrieval systems. Design/methodology/approach: The study is based on a quantitative research method and data was collected from the undergraduate students of medical colleges Islamabad Pakistan. The data were analyzed by Statistical Package for Social Science (SPSS) version 25 using Pearson correlation statistical test to identify the level of proficiency of correlation of variables and testing of the proposed hypothesis. Findings: The finding of the study shows that the medical students can enhance their IT skills to seek the information in this technology era. The medical institutional administration can develop the education development policy, traditional health education policy, funds allocating policy, health information literacy and collaborate with library staff for enhancing the services and to meet the information need of medical students. Practical implications: The conclusion of this study is very helpful to reduce the barriers between the students and the library staff. The findings of the study are also beneficial for the administration to improve and develop the strategies for enhancing the ILSs of medical students to achieve medical educational information in the age of technology. Therefore, all significant structures want to improve and to develop the environment of information seeking by medical students to achieve medical educational information. Social implications: Medical college library administrative management must be design useful a durable policy to come up with the technology development for digital literacy. The study reduces the barriers between the students and the library staff. Originality/value: The study is based on quantitative research method to find out ISB of medical students.